Casos y cosas: semanario popular (Vol. 1, No. 43) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: A nuestros detractores, La policia y las elecciones, Primera notificación, Electores en aeroplano, Ingratitud infame, Un obispado en iquitos, Femeninas

ENGLISH: To our detractors, police and elections, first notification, electors by airplane, infamous ingratitude, a bishopric in iquitos, feminine
Cases and things: popular weekly (Vol. 1, No. 43)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas